Analisis Semiotika Pada Film “Shigatsu Wa Kimi No Uso” Episode 3 Adegan 5 - Hidayat, Mohammad Syarif; Luthfie, Muhammad; Kusumadinata, Ali Alamsyah (Universitas Al Azhar Indonesia, 2022)
The anime series Shigatsu wa Kimi no Uso is an anime adapted from a manga (Japanese comic) with the same title as the main character named Arima. Based on the anime series shows, that there are implied meanings that can be analyzed by semiotic analysis as in episode 3 scene 5. Therefore, this study aims to analyze the meaning contained in episode 3 scene 5 of the anime series Shigatsu wa Kimi no Uso with the formula the problem